2006
DOI: 10.1002/ch.320
|View full text |Cite
|
Sign up to set email alerts
|

A new way of characterizing hypnotic interactions: Dyadic Interactional Harmony (DIH) questionnaire

Abstract: Aims: The validation of a new paper and pencil test (called Dyadic Interactional Harmony (DIH) questionnaire). Method: Data of two samples of standardized experimental hypnosis sessions (E1 and E2) are presented. In E1, 232 subjects (Ss) have been hypnotized using the standard protocol of SHSS:A; in E2, 110 Ss participated in group sessions of WSGC. Various well established measures of hypnosis (e.g. hypnotic susceptibility, AIM, PCI,) served as validating criteria for the 4 subscales of DIH: 1 Intimacy; 2 Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…Lynn and colleagues found increases in hypnotizability in a high-interpersonal condition in lows, but not in highs (Lynn et al, 1991). Finally, Varga and colleagues (Varga, Józsa, Bányai, & Gösi-Greguss, 2001) administered the Dyadic Interactional Harmony questionnaire (DIH) to two samples of healthy volunteers, along with standardized measures of hypnotizability. The DIH assesses four domains of perceived hypnotist-subject interaction: intimacy, communion, playfulness, and tension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lynn and colleagues found increases in hypnotizability in a high-interpersonal condition in lows, but not in highs (Lynn et al, 1991). Finally, Varga and colleagues (Varga, Józsa, Bányai, & Gösi-Greguss, 2001) administered the Dyadic Interactional Harmony questionnaire (DIH) to two samples of healthy volunteers, along with standardized measures of hypnotizability. The DIH assesses four domains of perceived hypnotist-subject interaction: intimacy, communion, playfulness, and tension.…”
Section: Resultsmentioning
confidence: 99%
“…A rare exception to a lack of attention to social factors in the field is the work of Éva Bányai, Katlin Varga, and their colleagues at the Eötvös Loránd University in Budapest, who have developed an impressive program studying hypnosis in the context of its social and interactional elements (Bányai, 1985, 1998; Varga, 2013; Varga, Banyai, & Gosi-Greguss, 1994; Varga, Banyai, Gosi-Greguss, & Tauszik, 2013; Varga, Józsa, Bányai, & Gösi-Greguss, 2009; Varga, Jozsa, Banyai, Gosi-Greguss, & Kumar, 2001). Much of the work completed by this group to date focuses on the assessment of the phenomenological experiences of the hypnotist and subject and their interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is also demonstrated that the hypnotist can be deeply involved at the level of experiences (Varga, Bányai, & Gősi-Greguss, 1999) as well. In other studies we found on the basis of inter-related analysis of data of subjects and hypnotists points and periods of concordances in the contents of their minds.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions are as follows (minor dimensions in parenthesis): Altered experience (altered body image, perception, meaning and time sense), Positive affect (joy, sexual excitement and love), Negative affect (anger, sadness and fear), Visual imagery (amount and vividness), Attention (direction and concentration), Self-awareness, Altered state of awareness, Internal dialogue, Rationality, Volitional control, Memory and Arousal. DIH The Dyadic Interactional Harmony Questionnaire (DIH) (Varga, Józsa, Bányai, & Gősi-Greguss, 2006) is a 50-item Likert-type scale ranging form 1 to 5 designed for measuring the interactive phenomenological relationship between hypnotist and subject. In our experiment we used a shorter (40 item (Spielberger, Gorsuch, & Lushene, 1970) is a 40 item questionnaire which measures the level of anxiety state and trait anxiety.…”
Section: Questionnairesmentioning
confidence: 99%
“…1 The inter subjective elements of online H-psychotherapy H-psychotherapy is an interactive, intersubjective process, and this understanding has slowly but steadily penetrated into professional discourse. 2,[39][40][41][42] Synchronized co-trance between the hypnotist and hypnotized has not only been theoretically discussed 43,44 but has also been empirically researched. 43,45 During a face-to-face interaction, the trance of the patient meets and synchronizes with the trance of the hypnotist through neurocognitive mechanisms of 'mirror neurons' 42,[46][47][48] mediated by vocal prosody, interpersonal synchrony, and nonverbal communication that takes place between hypnotist and hypnotized.…”
Section: (Question Suggestions)?'mentioning
confidence: 99%